(untitled) - Polchinski, Joseph Gerard (New York, 2005)
Volume 2: Superstring Theory and Beyond, begins with an introduction to supersymmetric string theories and goes on to a broad presentation of the important advances of recent years. The book first introduces the type I, type Ii, and heterotic superstring theories and their interactions. It then goes on to present important recent discoveries about strongly coupled strings, beginning with a detailed treatment of D-branes and their dynamics, and covering string duality, M-theory, and black hole entropy, and discusses many classic results in conformal field theory. The final four chapters are concerned with four-dimensional string theories, and have two goals: to show how some of the simplest string models connect with previous ideas for unifying the Standard Model; and to collect many important and beautiful general results on world-sheet and spacetime symmetries.
Keywords: Mô hình chuỗi,String models,Superstring theories.,Các lý thuyết siêu dây.